1999
DOI: 10.1086/501558
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Immunity in a Cohort of Pregnant Women

Abstract: To assess the rubella immune status of a cohort of high-risk pregnant women visiting a Midwestern clinic, we retrospectively studied 50 random pregnancies per year from 1990 through 1996. Of 350 patients analyzed, 53 (15.1%) were not immune to rubella, and vaccination opportunities were missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The prevalence rate of NRI demonstrated in this study appeared lower compared to previous studies in 1988 (7.5%–17.4%) [1], 1999 (15.4%) [2], and 2004 (9.1%) [3]. …”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The prevalence rate of NRI demonstrated in this study appeared lower compared to previous studies in 1988 (7.5%–17.4%) [1], 1999 (15.4%) [2], and 2004 (9.1%) [3]. …”
Section: Discussioncontrasting
confidence: 93%
“…A study in 1988 suggested that between 7.5 and 17.4% of pregnant women in the United States lack immunity to Rubella [1]. Similarly, a prevalence rate of 15.1% among pregnant women was reported in 1999 by investigators in Michigan [2]. In addition, a rate of 9.1% was found among women who attended prenatal care at Lejeune NC in 2004 [3].…”
Section: Introductionmentioning
confidence: 99%
“…A rubella-specific antibody titer of <10 IU/ml usually equates susceptibility, predisposing to fetal congenital rubella syndrome (CRS) if infection occurs in pregnancy. Rubella susceptibility is influenced by age, immunization compliance, gravidity and parity, and country of origin/birth [11][12][13][14][15][16][17][18], the last factor probably being the most important as Asians and Chinese have either accounted for the majority of rubella seronegative women, or an overall lower rate of seropositivity or antibody titer, compared with Caucasians in multiethnic communities [11,13,14,18,19]. Country of origin/birth could also impact through epidemiological factors, such as chronic hepatitis B virus (HBV) infection, which was associated with increased antenatal rubella seronegative status in Hong Kong [20].…”
Section: Introductionmentioning
confidence: 99%